584 Rehabilitation in Juvenile Idiopathic Arthritis with Hip Ankylosis (Balneo and PRM Research Journal, 2024)
Introduction: Juvenile idiopathic arthritis (JIA) is the most common type of arthritis in children and teens. The inflammation of various joints causes pain. Early diagnosis and management of the patients, which include medication and rehabilitation therapies, can reduce the onset of complications. Despite the progress in managing this disease, there are cases which present severe complications. Material and Methods: A 13-year-old girl, diagnosed with JIA in a paediatric service in 2019, who is under treatment with Sulfasalzine since diagnosis, presented in the Paediatric Rehabilitation Centre of Băile 1 Mai with inflammatory pain in both knees, gait impairment with need of wheelchair, limited function in hands, elbows, shoulders, knees and hips which worsened in 2022, due to low compliance to the treatment and no check-up with a paediatric rheumatologist. She had 8 admissions in the Paediatric Rehabilitation Centre between October 2022 and July 2023. The examination reveals that there is a severe limitation of mobility in both hips and knees, the hands’ small joints, elbows and shoulders. Laboratory tests were conducted showing no inflammatory markers. The radiographic finds sustained the changes encountered at the clinical examination.  During her admissions in the Paediatric Rehabilitation Centre, she underwent a complex rehabilitation program which consisted of kinetotherapy, hydrokinetotherapy, massage, occupational therapy and physical agents. The program was designed according to the needs and the disease activity. Pharmacological means were used for the management of pain. The results were limited and the ability of standing up and walking were not recovered. Conclusion: In conclusion, JIA is a complex disease, which needs an early diagnosis and an early management program, which comprises of pharmacological treatment, rehabilitation program. Team works is necessary for managing JIA cases. The lack of compliance, and inadequate medication can lead to disabling complications.